If \( C=3 x-4 \) and \( B=-x^{2}-9 x-9 \), find an expression that equals \( 2 C+2 B \) in standard form.
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To find \( 2C + 2B \), we start by calculating \( 2C \) and \( 2B \). 1. Calculate \( 2C \): \[ C = 3x - 4 \] \[ 2C = 2(3x - 4) = 6x - 8 \] 2. Calculate \( 2B \): \[ B = -x^2 - 9x - 9 \] \[ 2B = 2(-x^2 - 9x - 9) = -2x^2 - 18x - 18 \] 3. Now, we add \( 2C \) and \( 2B \): \[ 2C + 2B = (6x - 8) + (-2x^2 - 18x - 18) \] Combine like terms: \[ = -2x^2 + (6x - 18x) + (-8 - 18) \] \[ = -2x^2 - 12x - 26 \] Thus, the expression that equals \( 2C + 2B \) in standard form is: \[ \boxed{-2x^2 - 12x - 26} \]